Two-dimensional anionic zinc benzenedicarboxylates: Ionothermal syntheses, structures, properties and structural transformation - Tapala W. (2014)
The ionothermal synthesis of two intercalated two-dimensional zinc benzenedicarboxylates, EMIm2[Zn3(C6H 4(COO)2)3Cl2] (I) and BMIm 2[Zn3(C6H4(COO)2) 3Cl2] (II), employing the ionic liquids 1-ethyl-3-methylimidazolium chloride (EMIm-Cl) and 1-butyl-3-methylimidazolium chloride (BMIm-Cl) as solvents, is reported. Detailed characterization by X-ray diffraction, elemental analyses, vibrational and optical spectroscopies, and thermogravimetric analysis is described. The two compounds display an anionic two-dimensional structure with the composition [Zn3(C 6H4(COO)2)3Cl2] 2- which is intercalated and charge neutralized by the imidazolium cations. The compounds are remarkably stable: neither begins to lose mass until they are heated above 300 C, above which temperature ZnO is obtained. The structural transformation of the anionic layered compounds I and II to a neutral one-dimensional structure with the composition Zn(C6H 4(COO)2)(H2O)2 is described. The derived neutral compound shows better thermal robustness. Both the parent and the transformed structures display blue luminescence, arising from ligand centered π → π* and n → π* transitions. © 2013 Elsevier Ltd. All rights reserved.